IMPLEMENTASI KURIKULUM BERBASIS CINTA (KBC) DALAM KURIKULUM MERDEKA: ANALISIS PELUANG DAN TANTANGANNYA DI MTS KLUET UTARA - Rizki Rahmatillah; Silahuddin Rahmatillah (Al-Mudarris, 2026)
Contemporary Islamic education in Indonesia confronts a critical pedagogical tension: while the Merdeka Curriculum (Kurikulum Merdeka) offers structural flexibility for humanistic learning, the affective and relational dimensions of classroom interaction remain underdeveloped in both policy guidance and empirical research. The Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) a value-oriented pedagogical framework rooted in Islamic concepts of rahmah (compassion) and humanistic educational theory has emerged as a promising response to this gap. However, empirical research on KBC implementation within the Merdeka Curriculum context, particularly in Islamic junior secondary schools (Madrasah Tsanawiyah/MTs), remains scarce. This study addresses that gap through an exploratory qualitative case study design. Data were generated through in-depth interviews with three key informants, classroom observation, and document analysis, employing purposive sampling and thematic analysis with triangulation for credibility. Findings reveal that KBC implementation is at a preliminary stage, manifested through empathic teacher–student relational practices, positive emotional climate construction, humanistic feedback strategies, and the integration of Islamic rahmah values within Grade VII classrooms. Contextual enablers include alignment with Islamic pedagogy, local cultural norms, and the flexible architecture of the Merdeka Curriculum. Constraining factors include limited teacher conceptual literacy regarding KBC, absence of formal institutional guidelines, administrative burden, and insufficient professional development. This study contributes a preliminary conceptual model of KBC implementation and advances scholarly understanding of humanistic and rahmah-based pedagogy within Islamic secondary education.